(untitled) (Cadernos de Ética e Filosofia Política, 2018)
The Claude Lefort's ideas are applicable to brazilian reality after the Decade of 1980. This is the matching period to a broad democratic invention process: it was a product of social mobilization whose political flags turned into rights provided in the Constitution of 1988. On the other hand, the society failed to eliminate old dictatorial structures and to does not prevent the growth of an administrative power politically. This is what happens in the Brazilian Judiciary, that is sought for the population to commit rights, but it is still structured dictatorially and subjected to reforms that extend the administrative power under the pretext of ensuring legal certainty. The present work intends to relate the ideas of Lefort to the current context of strengtheningauthoritarian structures in the Judiciary, under the term of the democratic Constitution.